Voices from Margin: Theoretical Insights into Kaiser Haq's Ode on the Lungi - Prakash Chandra Biswas; Md. Jobaar Talukder (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This article investigates into Kaiser Haq’s poetic masterpiece, “Ode on the Lungi”, exploring its theoretical underpinnings and critical insights. The study employs a multidimensional approach, integrating postcolonial theories, literary analysis, and socio-cultural inquiry to unravel the symbolic significance of the lungi as a representation of subaltern voices. Haq strategically uses the lungi to challenge power imbalances, resist sartorial hegemony, and advocate for sartorial equality in the face of globalization. The research method includes qualitative analysis, theoretical engagement, and empirical evidence, aligning with postcolonial scholars such as Gramsci and Guha. The article underscores the poem’s role in breaking down divisive dichotomies and promoting democratic ideals. Through theoretical insights and close textual analysis, the study explores how the lungi, as a symbol of the underclass, resists aggressive modernism, demanding equal standing in the postcolonial and globalized reality. The poet’s call for “sartorial equality” transcends fashion, becoming a rallying cry for broader societal equality and recognition of marginalized voices. The research concludes by positioning Haq’s “Ode on the Lungi” as a powerful articulation of the subaltern voice within the complexities of postcolonial discourse.